Platelet to lymphocyte ratio as a new prognostic for patients with metastatic renal cell cancer. Issue 4 (14th April 2015) - Gunduz, Seyda; Mutlu, Hasan; Tural, Deniz; Yıldız, Özcan; Uysal, Mukremin; Coskun, Hasan Senol; Bozcuk, Hakan
Abstract Aim The objective of this study was to evaluate the blood platelet–lymphocyte ratio (PLR) for its prognostic value in patients with metastatic renal cell cancer (RCC). Methods We retrospectively reviewed 100 patients diagnosed with metastatic RCC previously treated with tyrosine kinase inhibitors from three centers. We assessed the prognostic value of pretreatment PLR and other clinical and laboratory parameters based on univariate and multivariate analyses. Results Median progression‐free survival (PFS) was 7.3 months and median overall survival (OS) was 15.3 months. Multivariate analysis revealed that PFS is significantly affected by ECOG PS (P = 0.047), PLR (P = 0.029) and calcium level (P = 0.023). Median PFS was 13.9 versus 5.3 months in patients with PLR ≤ 210 versus PLR > 210 (log rank; P = 0.001). Median OS was 25.9 versus 10.9 months with PLR ≤ 210 versus PLR > 210 (log rank; P = 0.013). Conclusions This study shows that increased pretreatment PLR is an independent prognostic indicator in patients with metastatic RCC who use tyrosine kinase inhibitors.